Risk factors contributing to inland water transport passenger ferry accidents in Bangladesh - Sahed Hossen Sajib (Journal of Safety and Sustainability)
Bangladesh possesses the geographical traits to make a model inland water transport (IWT) system globally, unfortunately, it is prone to accidents and casualties. This study presents an outline of risk factors liable for the IWT passenger ferry accident in the southern route of Bangladesh that was not examined by the existing studies. The factors were grouped into five broad categories and independently assessed their risk level based on their risk score. Findings indicate that the heat-sensitive products and raw materials category contains the highest number of critical risk factors where warning facilities and safety exits concurrently scored the maximum risk value. Other critical risk factors include evacuation routes, siren systems, gas cylinders, kitchen rooms, fire detection systems, hospital facilities, berthing competition, critical bottleneck, political intervention, high crowds on the quay and unpublished accident reports. In the high-risk level, the passenger boarding competition scored the highest risk value. The spaces and stairs of the first-class area, the absence of first aid facilities, unnecessary horns at the quay, investigation committee members, no safety instructions by the crew and the fueling process are also at high-risk levels. The major medium-risk level factors were air conditioners, burnable lading, risky owner groups and loading/unloading checks by traffic officers. Factors such as ship documentation, river crossing spots, searchlight coverage and uncertain water level conditions were underscored in low-risk levels. Furthermore, an accident hotspot was identified in the Meghna River near Horina (Chandpur district) where the traffic is high and many rivers intersect. The rescue/reconstruction event of the IWT accident in Bangladesh was also scrutinized. The accident of the IWT passenger ferry is a complex interactivity among these natural and human factors. Reducing or eliminating these factors in IWT can contribute to a more sustainable transport system for Bangladesh.